Synthesis of new hydrophilic rhodamine based enzymatic substrates compatible with droplet-based microfluidic assays. Issue 39 (2nd May 2017) - Fenneteau, Johan; Chauvin, Dany; Griffiths, Andrew D.; Nizak, Clément; Cossy, Janine
Abstract : The modification of rhodamine core with a hydrophilic tag yields new fluorogenic enzymatic substrates compatible with high-throughput screening using droplet-based enzymatic assay. Abstract : Here we report the conception, synthesis and evaluation of new hydrophilic rhodamine-based enzymatic substrates for detection of peptidase activity compatible with high-throughput screening using droplet-based microfluidics.